Are Innovating Firms Victims or Perpetrators? Tax Evasion, Bribe Payments, and the Role of External Finance in Developing Countries - Ayyagari, Meghana; Demirgüç-Kunt, Asli; Maksimovic, Vojislav (2012)
This paper investigates corruption and tax evasion and their firm-level determinants across 25,000 firms in 57 countries, a large fraction of which are small and medium enterprises in developing countries. Firms that pay more bribes also evade more taxes. Corruption acts as a tax on innovation, particularly that of small and young firms. Innovating firms pay a larger percentage of their revenues in bribes to government officials than non-innovating firms. They do not, however, pay more protection money to private parties than other firms. Comparing the magnitudes of bribes and taxes evaded, innovating firms and firms that use formal finance are more likely to be net victims. The findings point to the challenges facing innovators in developing countries and the role of banks in curbing corruption and tax evasion.